Theoretical foundation of the study of the region image - Valitova, Z.Kh.; Kadatskaya, N.; Yessimova, A.B. (KSU publ., 2020)
Modern theoretical foundations of studying the phenomenon of the region image are considered in the article. Image-relevant concepts such as «image», «self-image», «brand» are analyzed. Attention is also paid to various notions of definitions of the concept «region», which depend on disciplinary specialization. The authors note that in modern research the region ceases to be only physical space and attempts to apply constructionist theories in the analysis of the region phenomenon. The theoretical consideration of the region image, first of all, emphasizes the subjective importance of the image phenomenon, which allows to consider the region as a variable, which boundaries are defined not only physically, but also mentally.
Keywords: image; brand; character; region; theories; concepts